PEMETAAN POTENSI ENERGI ANGIN DI SUMATERA UTARA (Mapping of Wind Energy Potential in North Sumatera Province) - Andreas Sembiring; Riswanti Sigalingging; Saipul Bahri Daulay (Universitas Sumatera Utara, 2018)
ABSTRACT Today the world is facing a fossil energy crisis, especially Asian countries including Indonesia. Indonesia, especially North Sumatra has the potential for the development of renewable energy, especially wind energy. The research was conducted in June - August 2017 in seven districts of Langkat, Serdang Bedagai District, Labuhan Batu Regency, Asahan Regency, Tapanuli Tengah Regency, Samosir Regency and Karo Regency, by measuring wind speed and temperature for 3 days in each district, each location point for 12 hours per day. The data of the research results were then calculated by the equation that has been determined. The results showed that the regency with the highest wind speed, total power and total energy value was Samosir Regency with an average wind speed of 5.89 m/s, the average specific power of 170.78 Watt and the average total energy was 7377.67 KWh. The regency with the lowest wind speed, the lowest total power and total energy was Karo Regency with an average wind speed value of 0.95 m/s, the average specific power of 0.86 Watt and the total average energy was 37.14 KWh. The total value of wind speed, total power and total energy for the province of North Sumatra were 3.34 m/s, 52.20 Watt and 2255.07 KWh. Based on the results of data analysis conducted, the Province of North Sumatra had a wind speed of 3.34 m/s and included in the category of small-scale wind speed. Keywords: Wind Energy, Wind Speed. ABSTRAK Dewasa ini dunia sedang dihadapkan pada krisis energi fosil, khususnya negara-negara Asia termasuk Indonesia. Indonesia khususnya Sumatera Utara memiliki potensi untuk pengembangan energi terbaharukan khususnya energi angin. Penelitian ini dilakukan pada bulan Juni – Agustus 2017 pada tujuh kabupaten yaitu Kabupaten Langkat, Kabupaten Serdang Bedagai, Kabupaten Labuhan Batu, Kabupaten Asahan, Kabupaten Tapanuli Tengah, Kabupaten Samosir dan Kabupaten Karo, dengan mengukur kecepatan angin dan suhu selama 3 hari di masing-masing titik lokasi selama 12 jam per harinya. Data hasil penelitian selanjutnya dihitung dengan persamaan yang sudah ditetapkan. Hasil penelitian menunjukkan kabupaten dengan nilai kecepatan angin, daya spesifik dan energi total tertinggi adalah Kabupaten Samosir dengan nilai kecepatan angin rata-rata 5,89 m/s, daya spesifik rata-rata 170,78 Watt dan energi total rata-rata adalah7377,67 KWh. Kabupaten dengan nilai kecepatan angin, daya spesifik dan energi total terendah adalah Kabupaten Karo dengan nilai kecepatan angin rata-rata 0,95 m/s, daya spesifik rata-rata 0,86 Watt dan energi total rata- rata adalah 37,14 KWh. Total nilai keceptan angin, daya spesifik dan energi total untuk provinsi Sumatera Utara adalah 3,34 m/s, 52,20 Watt dan2255,07 KWh. Berdasarkan hasil analisis data yang dilakukan, provinsi Sumatera Utara memiliki kecepatan angin 3, 34 m/s dan masuk dalam kategori kecepatan angin skala kecil. Kata kunci: Energi Angin, Kecepatan Angin.